2021
DOI: 10.1039/d0ea00022a
|View full text |Cite
|
Sign up to set email alerts
|

Unique calibration of passive air sampling for field monitoring of PAHs with polyethylene thin films across seasons and locations

Abstract: Although passive sampling has been applied to determine concentrations of semi-volatile organic chemicals such as polycyclic aromatic hydrocarbons (PAHs) in air and water for about two decades and is well...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 74 publications
1
16
0
Order By: Relevance
“…Integration over half a year naturally leads to a loss of dynamics within this exchange process and thus adds some uncertainty especially for the LMW PAHs (Fln and Phe). In a previous study, we show that the average atmospheric concentrations remain relatively stable throughout seasons (comparing May and August, as well as November and February) during two consecutive years . For the soils, the ex situ batch experiment illustrates quite slow desorption kinetics, which exceed 4 months to equilibrate.…”
Section: Resultsmentioning
confidence: 55%
See 4 more Smart Citations
“…Integration over half a year naturally leads to a loss of dynamics within this exchange process and thus adds some uncertainty especially for the LMW PAHs (Fln and Phe). In a previous study, we show that the average atmospheric concentrations remain relatively stable throughout seasons (comparing May and August, as well as November and February) during two consecutive years . For the soils, the ex situ batch experiment illustrates quite slow desorption kinetics, which exceed 4 months to equilibrate.…”
Section: Resultsmentioning
confidence: 55%
“…Seasonal variations of organic pollutants in the atmosphere (or the vegetation layer above the ground) have been related to plants and plant growth as a buffering effect by numerous studies. ,,, Thomas et al and Gouin et al observe a decrease of atmospheric PCB concentrations simultaneous to an increase of biomass, and Liu et al measure a decrease of PAHs in air during the growing season. In our earlier study, no indication of such a scavenging effect could be observed and instead atmospheric concentrations were rather stable during the growing season (May to August). Consequently, in the present study, the seasonal variation of PAH concentrations in air and the concentration gradient across the soil–atmosphere interface can mostly be explained by changing temperature as well as primary emission rates due to increased combustion during the cold season. ,,, …”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations